Lost and found: a rare case of subcutaneous migration of neglected missing intrauterine contraceptive device complicated by anterior abdominal wall chronic sinus formation - Mohamed Dawood (The Egyptian Journal of Radiology and Nuclear Medicine)
Abstract Background Intrauterine contraceptive device (IUD) is an effective and safe method for reversible long-acting contraception. The incidence of perforation at insertion time has been reported to be 1.3 to 1.6 per 1000 insertions. Although considered a rare complication, it can cause serious complications that can require surgical intervention to retrieve the missing IUD. Presentation of case We present the case of a 37-year-old female patient who had a history of three IUD insertions, one of which went missing and was found years later in the subcutaneous tissue of the lower anterior abdominal wall causing chronic sinus formation for 4 years. Conclusion Uterine perforation and migration is an uncommon complication of IUDs and should be considered in all missing IUD threads. Accurate diagnosis and proper management are essential to prevent major complications.